2016
DOI: 10.1021/acs.jpcc.5b11279
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Modification of Free-Floating Few-Layer Graphene by Aryldiazonium Ions: Electrochemistry, Atomic Force Microscopy, and Infrared Spectroscopy from Grafted Films

Abstract: Free-floating, and copper-supported, few-layer graphene sheets were spontaneously modified from an aqueous solution containing nitrobenzenediazonium ions. The infrared spectra of the chemically modified (copper etched) free-floating graphene were measured in transmission mode by manipulating the sheets onto a KBr disc. The major advantage to this method is the ability to release the graphene sheets off the disc to refloat on a water bath, allowing the graphene to be further modified or deposited onto a new sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 49 publications
(87 reference statements)
0
39
0
Order By: Relevance
“…This, it can be concluded that the basic process is a diazonium salt or a diazo compound formed by diazotization of an aromatic amine-containing substance having a reactive functional group, and an electron is removed to form a free radical aer deaeration. 77 Then, a double bond addition reaction with C]C is carried out to form a new C-C single bond, which is linked to the derivative of benzene having a reactive functional group by a sigma bond, distributed on the surface, and then further, graphene with is reactive functional groups undergo functional modication with graphene oxide.…”
Section: Covalent Functionalizationmentioning
confidence: 99%
“…This, it can be concluded that the basic process is a diazonium salt or a diazo compound formed by diazotization of an aromatic amine-containing substance having a reactive functional group, and an electron is removed to form a free radical aer deaeration. 77 Then, a double bond addition reaction with C]C is carried out to form a new C-C single bond, which is linked to the derivative of benzene having a reactive functional group by a sigma bond, distributed on the surface, and then further, graphene with is reactive functional groups undergo functional modication with graphene oxide.…”
Section: Covalent Functionalizationmentioning
confidence: 99%
“…The electrode area was measured by optical imaging and software evaluation of the epoxy edges using ImageJ. We have previously established that solution ingress to the backside of the electrode occurs; thus, both sides of the graphene sheet are contacting the electrolyte . Hence, all figures are given with respect to double the observable measured electrode area.…”
Section: Resultsmentioning
confidence: 99%
“…The number of graphene layers was determined by the reduction in transparency between 800 and 600 nm of the graphene sheet mounted onto a quartz slide (Cary 50 UV–vis spectrometer) . The quality of the graphene sheets was assessed using Raman spectroscopy as described elsewhere, and as expected, there was a small D band in the spectrum, indicative of some defective structure in the sheets. , …”
Section: Experimental Methodsmentioning
confidence: 99%
“…However, most of the published works on the electrografting by aryldiazonium reduction have considered the analysis of the chemisorbed film in the framework of their physical and chemical properties, where spectroscopic and voltam-metric techniques have been mainly used. Further studies showed that this kind of surface modification can also be achieved without electrochemical induction [13], which has been of interest for the functionalization of carbon materials upon the form of solids and powders [14][15][16]. The first contribution on this spontaneous grafting without electrochemical activation was made by Pinson et al [13] who reported the attachment of nitrophenyl radicals to solid substrates of glassy carbon, cupper, iron, nickel, and zinc, just by dipping the electrodes in solutions bearing different concentrations of 4-nitrophenyldiazonium tetrafluoroborate.…”
Section: Introductionmentioning
confidence: 99%